A male mouse model of WIN 55,212–2 self-administration to study cannabinoid addiction - Cajiao-Manrique, María del Mar; Maldonado, Rafael; Martín-García, Elena (Frontiers in Pharmacology, 2023)
We have established for the first time a mouse model of cannabinoid addiction using WIN 55,212-2 intravenous self-administration (0.0125 mg/kg/infusion) in C57Bl/6J mice. This model allows to evaluate the addiction criteria by grouping them into 1) persistence of response during a period of non-availability of the drug, 2) motivation for WIN 55,212-2 with a progressive ratio, and 3) compulsivity when the reward is associated with a punishment such as an electric foot-shock, in agreement with the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5). This model also allows to measure two parameters that have been related with the DSM-5 diagnostic criteria of craving, resistance to extinction and reinstatement, and two phenotypic traits suggested as predisposing factors, impulsivity and sensitivity to reward. We found that 35.6 % of mice developed the criteria of cannabinoid addiction, allowing to differentiate between resilient and vulnerable mice. Therefore, we have established a novel and reliable model to study the neurobiological correlates underlying the resilience or vulnerability to develop cannabinoid addiction. This model included the chemogenetic inhibition of neuronal activity in the medial prefrontal cortex to the nucleus accumbens pathway to assess the neurobiological substrate of cannabinoid addiction. This model will shed light on the neurobiological substrate underlying cannabinoid addiction.